What Causes Product Returns in Online Purchases? A Review and Research Agenda - Kar, Brajaballav; Tripathy, Arvind; Pathak, Mallika Devi (Prabandhan: Indian Journal of Management, 2022)
The growth in e-commerce is an opportunity, but the resulting product return is a challenge. The complex and multidimensional nature of product return influences the manufacturer, product, retailer, channel, return policy, logistics service provider, customers, or any combination thereof. Compared to other economies, the level of product return is high in an emerging economy like India, which prompted this structured literature review. The literature pointed to the product return as a ‘moment of truth’ involving emerging practices like buy online return in store (BORIS), wardrobing, renting, bracketing, home-try programs, subscription than buy, and sending of curated choices to customers, which drastically change purchases as well as returns. The return policy, dynamic pricing, website design and usability, product category, and inventory visibility influence product returns. Fraudulent returns are of concern compared to legitimate returns. Customer attitude, informationseeking behavior, post-purchase dissonance, individual and group decisions, and different temporal variables make customers sensitive to return. Additionally, the product utility, competitive and comparative value, perceived fairness, and customer empowerment also influence returns. Switching physical processes to online creates an additional challenge. A comprehensive understanding of product return in online purchase situations is expected to create value for customers and agents in the value chain. Effective information sharing across the value chain and within an organization can adjust the inevitable product returns to an optimal level and ensure multi-channel interoperability.